Numerical investigation for the fatigue performance of reinforced concrete beams strengthened with external prestressed HFRP sheet. (20th March 2020) - Wang, Xiaomeng; Zhou, Chuwei; Ai, Jun; Petrů, Michal; Liu, Yao
Highlights: The fatigue performance of RC beams strengthened with C/GFRP is studied. Different material models are evaluated to describe the fatigue behavior of the beams. The model can be applied in analysis of other FRP strengthened structures. Abstract: External FRP (Fiber Reinforced Polymer) strengthening method has been considered to be an effective way to restore or increase the capacity of RC (Reinforced Concrete) beams. This study focuses on numerical simulating the fatigue performance of HFRP (Hybrid Fiber Reinforced Polymer) strengthened RC beam. Beams are pre-cracked first, then strengthened by HFRP, and subjected to fatigue loading. The test variable is the prestress of HFRP. Stress distribution and damage development of pre-cracking, strengthening and fatigue loading process are analyzed. The user-subroutine UMAT in Abaqus is used for implementation of the constitutive models of component materials. The simulation results show good agreements with experimental data. The failure of both reference beam and strengthened beams is found caused by fatigue fracture of the longitudinal steel bar. Therefore, the stress amplitude of the longitudinal steel bar is the dominant factor of the fatigue life of RC beams. Prestressed HFRP can significantly reduce the stress magnitude of longitudinal steel bar and suppress crack propagation, thus improve the fatigue life of the strengthened RC beam. In an appropriate range, elevating prestress level can prolong fatigue life of strengthened RC beam.